Prática docente com tecnologias móveis digitais nos anos iniciais do ensino fundamental - Menezes, Danielle Santos (2024)
The actual society is immersed in a digital culture that involves the influence of digital mobile technologies in everyday life, playing an important role in communication, entertainment, labor, education, and health. With the Covid-19 pandemic and social distancing, these technologies have become important, especially in education, as there has been a transition to the Ensino Remoto Emergencial (ERE). Thus, mobile devices such as smartphones, notebooks, and tablets have become a useful resource for teachers and students to connect, share materials, and participate in videoconferences asynchronously and synchronously. In this sense, the present study had as its main objective to understand the use of mobile technologies in teaching practices in the initial years of elementary school of the county education network in the city of Lagarto/SE. This is a qualitative research, characterized as descriptive with an exploratory approach, carried out from the school context of three institutions in the public network of Lagarto, city located in the south-central region of the State of Sergipe, located in the Northeast, with the participation of five teachers. To this end, the following guiding question was asked: what factors prevent the use of digital mobile technologies in teaching practices in the municipal education network of the city of Lagarto/SE? With this in mind, the following means were used to produce data: unstructured interviews conducted in person and non-participant observation. As for data analysis, it was done from the perspective of Bardin's (2016) content analysis method and through data triangulation, according to Santos et al. (2020). This study had contributions from the Núcleo de Pesquisa em Comunicação e Tecnologia (NUCA/CNPq/UFS), linked to the Programa de Pós-graduação em Educação da Universidade Federal de Sergipe (PPGED/UFS), in the line of research on the Formação e Prática Docente. The results indicate that digital mobile technologies are being used in the teaching practice of the participants in this research, however, with challenges; among them: inadequate infrastructure, little practical teacher training and slow/poor technological devices, which are sent to the school, according to the teachers participating in the research.